2019
DOI: 10.1186/s12014-019-9252-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism impairment in patients with sepsis secondary to hospital acquired pneumonia, a proteomic analysis

Abstract: Background Sepsis is a dysregulated host response to infection and a major cause of death worldwide. Respiratory tract infections account for most sepsis cases and depending on the place of acquisition, i.e., community or hospital acquired infection, differ in etiology, antimicrobial resistance and outcomes. Accordingly, the host response may be different in septic patients secondary to community-acquired pneumonia and hospital acquired pneumonia (HAP). Proteomic analysis is a useful approach to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 52 publications
(59 reference statements)
4
65
0
1
Order By: Relevance
“…Previous studies have reported that lipid metabolism impairment may be involved in the pathogenesis of sepsis secondary to pneumonia and in uenza [8][9][10]. Similarly, recent studies observed dyslipidemia in patients infected with SARS-CoV-2, using MS analysis [6,7] and routine laboratory lipid tests [11], indicating that blood lipid might involve in the pathogenesis of COVID-19.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have reported that lipid metabolism impairment may be involved in the pathogenesis of sepsis secondary to pneumonia and in uenza [8][9][10]. Similarly, recent studies observed dyslipidemia in patients infected with SARS-CoV-2, using MS analysis [6,7] and routine laboratory lipid tests [11], indicating that blood lipid might involve in the pathogenesis of COVID-19.…”
Section: Discussionmentioning
confidence: 90%
“…Focusing on apolipoproteins, the authors demonstrated a decrease of some apolipoproteins (ApoA-I, ApoA-II, ApoA-IV, ApoB, ApoC-I, ApoC-II, ApoC-III, and ApoE). A recent study on the lipidome showed a decrease in phospholipid concentration in hospital-acquired pneumonia [83].…”
Section: Hdl Function In Inflammatory Statementioning
confidence: 97%
“…Previous studies have found that lipid metabolism impairment may involve in the pathogenesis of sepsis secondly to pneumonia and in uenza [10][11][12]. Similarly, recent studies observed the dyslipidemia in the patients infected with SARS-CoV-2 by MS analysis, especially in the severe cases [7][8][9], which reminded us that blood lipid might serve as a maker for the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 77%